2002
DOI: 10.1046/j.1365-246x.2002.01625.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetostratigraphic results from impact crater Lake El'gygytgyn, northeastern Siberia: a 300 kyr long high-resolution terrestrial palaeoclimatic record from the Arctic

Abstract: Summary A 12.7 m long sedimentary record recovered from Lake El'gygytgyn, located in a meteorite impact crater created 3.6 Ma in Late Cretaceous igneous rocks on Chukotka Peninsula, northeast Siberia, has been analysed for its palaeo‐ and rock‐magnetic properties. Continuous high resolution (1 mm) measurements of magnetic susceptibility yielded successions of pronounced lows and highs. Analyses of the rock‐magnetic properties by low and high temperature runs of magnetic susceptibility, determination of hystere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 26 publications
(29 reference statements)
4
98
0
Order By: Relevance
“…2), recovered in 1998, was deduced from tuning regional insolation with magnetic susceptibility, biogenic silica, total organic carbon and TiO 2 values in the sediments (Nowaczyk et al, in press; Melles et al, in press). It is confirmed by pollen analyses, AMS radiocarbon and MAAD polymineral fine-grain IRSL dating (Nowaczyk et al, 2002;Nowaczyk et al, in press;Forman et al, in press).…”
Section: Age Modelmentioning
confidence: 70%
“…2), recovered in 1998, was deduced from tuning regional insolation with magnetic susceptibility, biogenic silica, total organic carbon and TiO 2 values in the sediments (Nowaczyk et al, in press; Melles et al, in press). It is confirmed by pollen analyses, AMS radiocarbon and MAAD polymineral fine-grain IRSL dating (Nowaczyk et al, 2002;Nowaczyk et al, in press;Forman et al, in press).…”
Section: Age Modelmentioning
confidence: 70%
“…Weathering of the rocks is largely controlled by the presence or absence of permafrost . Fluvial transport and sedimentation is limited to summer periods when air temperatures are above 0 • C and the ice cover on the lake is disintegrating (Nolan and Brigham-Grette, 2002). During expeditions in 1998 and 2003, designed as pilot studies for the ICDP-drilling of Lake El'gygytgyn, two long sediment cores, PG1351 and Lz1024, were recovered from the lake centre at a water depth of 175 m (Fig.…”
Section: Settings and Materialsmentioning
confidence: 99%
“…The sediment consists of alternations of brownish and greenish nonlaminated and laminated greyish silt and clay; including some turbidites with thicknesses of up to 45 cm (Juschus et al, 2009). Former investigations on core PG1351 (Nowaczyk et al, 2002Melles et al, 2007;Minyuk et al, 2007) revealed that anoxic and laminated conditions primarily occur during periods of perennial ice cover and oxic and nonlaminated conditions occur when open water controls mixing of the water body during summer times . In intervals with prevailing anoxic conditions reductive dissolution of magnetite was observed whereas organic matter is well preserved.…”
Section: Settings and Materialsmentioning
confidence: 99%
See 2 more Smart Citations